Effect of freeze-thaw cycles on the physicochemical properties and frying performance of frozen Youtiao dough. (30th August 2022) - Bai, Ni; Guo, Xiao-Na; Xing, Jun-Jie; Zhu, Ke-Xue
Highlights: Youtiao had a lower specific volume and higher hardness after freeze–thaw cycles. The maximum resistance and extensibility of frozen youtiao dough decreased. The storage and loss modulus decreased while the creep compliance increased. The SDS extractable protein and free SH content increased. Micromorphology observed a loose dough structure and fractured protein network. Abstract: The impact of freeze–thaw cycles on the physicochemical properties and frying performance of frozen Youtiao dough with chemical leavening agent was investigated. The specific volume of Youtiao made from frozen dough decreased by 66% after 4 freeze–thaw cycles. Meanwhile, the hardness and puncture force showed increasing trends, and the fibrous structure became unclear. The extensibility, storage modulus (G′) and loss modulus (G′′) of frozen Youtiao dough decreased during freeze–thaw cycles, while the creep compliance increased. Changes in rheological properties demonstrated that frozen Youtiao dough was more deformable and its strength was weakened. Moreover, the sodium dodecyl sulfate (SDS) extractable protein and free sulfhydryl content increased, revealing that protein was depolymerized. The loose structure with large pores and fractured protein network were observed by micromorphology. Freeze-thaw cycles had a detrimental effect on the Youtiao quality, which was related to the deterioration of rheological properties and protein structure of frozen Youtiao dough.